Lower bounds for the volume of the image of a ball - Klishchuk, B. A.; Salimov, R. R. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.5 We consider ring $Q$-homeomorphisms with respect to $p$-modulus inthe space $\Bbb R^{n}$ as $p>n$. We obtain a lower bound for the volume of the image of a ball under these mappings. We solve the extremal problems of minimization of functionals of the volume of the image of a ball and the area of the image of a sphere.